2017
DOI: 10.1016/j.gendis.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D receptor gene polymorphism (VDR) with vitamin D deficiency, metabolic and inflammatory markers in Egyptian obese women

Abstract: Vitamin D deficiency might contribute to the pathogenesis of metabolic syndrome and could cause immune disturbance. The aim of this study is to analyze the associations between Vitamin D receptor (VDR) gene polymorphism, serum 25-hydroxy vitamin D, metabolic and inflammatory biomarkers in Egyptian obese women. The study included 201 obese women with vitamin D deficiency and 249 obese matched age healthy controls with sufficient vitamin D levels. Their age ranged between 25 and 35 years. Inflammatory biomarkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 36 publications
5
40
2
Order By: Relevance
“…Several studies have documented that the onset of osteoporosis is caused by VDR gene polymorphisms [81]. VDR gene polymorphisms are also associated with other diseases like breast cancer [105], diabetes [106], myocardial infarction [107], and metabolic syndrome and inflammation [108].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented that the onset of osteoporosis is caused by VDR gene polymorphisms [81]. VDR gene polymorphisms are also associated with other diseases like breast cancer [105], diabetes [106], myocardial infarction [107], and metabolic syndrome and inflammation [108].…”
Section: Discussionmentioning
confidence: 99%
“…6,[14][15][16][17][18][19][20]30,33,34 Some studies have reported a link between vitamin D status, response to vitamin D supplementation, and VDR gene polymorphisms. [35][36][37][38][39] Studies by Martineau et al, Søborg et al, and Lewis et al on pulmonary tuberculosis patients have shown that administration of high doses of VitD have no effect on sputum conversion time when assessed in relation to Fok1 genotype, 35 while other VDR SNPs appeared to influence the response to VitD supplementation. 36,37 The Karpinski study on low-energy bone fractures has demonstrated that ApaI polymorphism recessive "aa" and TaqI polymorphism dominant "TT" genotypes are associated with higher levels of vitamin D in serum.…”
Section: Resultsmentioning
confidence: 99%
“…It is predicted that there will be an alarming increase in the incidence of diabetes from 382 million (8.3%) in 2013 to 592 million (10.1%) in 2035. The previous study has shown a strong correlation between the VDR polymorphisms and T2DM-associated metabolic parameters [12]. To briefly explain, the human VDR gene is located on chromosome 12q13.1.…”
Section: Discussionmentioning
confidence: 99%